The Taylor Matrix Method for Approximate Solution of Lane-Emden Equation with index-n - Guler, Coskun; Emiroglu, Ibrahim; Tasci, Fatih; Sivri, Mustafa (NATURAL SCIENCES PUBLISHING CORPORATION, 2013)
Many problems in mathematical physics can be formulated as an equation of Lane-Emden type. There are many methods for the solution of this equation. One of these methods is the Taylor matrix method. The only types of nonlinear equations that this method has been applied so far are the Riccati and Abel equations. In this study, an algorithm based on the Taylor matrix method is proposed and applied to the nonlinear Lane-Emden equation with index-n. An example is also given.
Keywords: Lane-Emden equation; the Taylor matrix method; Nonlinear differential equations; ALGORITHM; Mathematics; Physics